Investigating Serum sHLA-G Cooperation With MRI Activity and Disease-Modifying Treatment Outcome in Relapsing-Remitting Multiple Sclerosis - Amoriello, Roberta; Rizzo, Roberta; Mariottini, Alice; Bortolotti, Daria; Gentili, Valentina; Bonechi, Elena; Aldinucci, Alessandra; Carnasciali, Alberto; Peruzzi, Benedetta; Repice, Anna Maria; Massacesi, Luca; Fainardi, Enrico; et al. (Frontiers in Neurology, 2022)
Relapsing-remitting Multiple Sclerosis (RRMS) is a demyelinating disease in which pathogenesis T cells have a major role. Despite the unknown etiology, several risk factors have been described, including a strong association with Human Leukocyte Antigen (HLA) genes. Recent findings showed that HLA class I-G (HLA-G) may be tolerogenic in MS, but further insights are required. To deepen the HLA-G role in MS inflammation, we measured soluble HLA-G (sHLA-G) and cytokines serum level in 27 RRMS patients at baseline and after 12 and 24 months of Natalizumab (NTZ) treatment. Patients were divided into high (sHLA-G>20 ng/mL), medium (sHLA-G between 10-20 ng/mL) and low (sHLA-G<10 ng/mL) producers. Results showed a heterogeneous distribution of genotypes among producers, with no significant differences between groups. A significant decrease of sHLA-G was found after 24 months of NTZ in low producers carrying the +3142 C/G genotype. Finally, 83.3% of high and 100% of medium producers were MRI-activity free after 24 months of treatment, compared to 63.5% of low producers. Of note, we did not find any correlation of sHLA-G with peripheral cell counts or cytokines level. These findings suggest that serum sHLA-G level may partly depend on genotype rather than peripheral inflammation, and that may have impacted on MRI activity of patients over treatment.